The Responsibility of Subsidiaries for The Bankruptcy of Parent Companies: A Comparative Study in Indonesian & Singaporean Laws - Putri Mufidah; Suherman Suherman (Jurnal Daulat Hukum, 2026)
This study is motivated by the ambiguity of regulations regarding the legal status of corporate groups in Indonesia in the event of parent company bankruptcy. Although the principle of separate legal entity is universally recognized, business practices often reveal strong financial interdependence between parent and subsidiary companies. The main issues examined are the legal position of subsidiaries vis-à-vis parent companies that have been declared bankrupt and how this compares in the legal systems of Indonesia and Singapore. This research positions itself as a comparative law study that examines the consistency of the application of principles and doctrines in complex corporate structures. Using a normative juridical method through a legislative approach and comparative study, this article analyzes the regulatory framework of the Limited Liability Company Law and the Bankruptcy Law in Indonesia compared to the Companies Act and the Insolvency, Restructuring, and Dissolution Act (IRDA) 2018 in Singapore. The results of the study show that Indonesia still relies on casuistic judicial interpretations, as seen in the cases of PT Sritex and PT Hanson International Tbk, which create legal uncertainty for subsidiaries. In contrast, Singapore offers greater normative clarity through strict control parameters and mechanisms that protect insolvent subsidiaries. This study concludes that Indonesia needs legal reforms that explicitly regulate corporate group regimes to minimize risks and provide legal certainty.